2014
DOI: 10.3389/fonc.2014.00246
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Breast Cancer: High Incidence of Detection of Mixed Human Cytomegalovirus Genotypes Associated with Disease Pathogenesis

Abstract: Inflammatory breast cancer (IBC) is a highly metastatic, aggressive, and fatal form of breast cancer. Patients presenting with IBC are characterized by a high number of axillary lymph node metastases. Recently, we found that IBC carcinoma tissues contain significantly higher levels of human cytomegalovirus (HCMV) DNA compared to other breast cancer tissues that may regulate cell signaling pathways. In fact, HCMV pathogenesis and clinical outcome can be statistically associated with multiple HCMV genotypes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 76 publications
(101 reference statements)
0
28
0
Order By: Relevance
“… 34 The gN3b genotype was reported as the most prevalent genotype in a study of patients with inflammatory breast cancer. 35 However, gN3 was not found to be frequently associated with other populations of immunocompromised patients. By contrast, gN1 has been frequently observed among solid organ transplant patients and acquired immunodeficiency syndrome patients.…”
Section: Discussionmentioning
confidence: 91%
“… 34 The gN3b genotype was reported as the most prevalent genotype in a study of patients with inflammatory breast cancer. 35 However, gN3 was not found to be frequently associated with other populations of immunocompromised patients. By contrast, gN1 has been frequently observed among solid organ transplant patients and acquired immunodeficiency syndrome patients.…”
Section: Discussionmentioning
confidence: 91%
“…They reported detection of more HCMV DNA in IBC tissues compared to IDC, and higher HCMV IgG titers in IBC patients compared to IDC patients [ 72 ]. In a follow-up study, they assessed viral genotypes and found a correlation between mixed phenotypes and disease progression, notably lymphovascular invasion and formation of lymphatic emboli in IBC patients, but not in women with other forms of breast cancer [ 73 ]. The findings suggest that HCMV may be more closely associated with specific subtypes of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[8] and in carcinoma tissue of malignant glioma [9] and prostate cancer [10]. CMV is reported to have an oncogenic potential role in breast cancer [11] and to have possible causal relationship with mucoepidermoid carcinoma [12] .…”
Section: Discussionmentioning
confidence: 99%